2010
DOI: 10.1007/s12011-010-8647-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Inorganic Zn and Mn and their Interactions on the Performance of Broiler Chicken, Mineral Bioavailability, and Immune Response

Abstract: The purpose of this study was to investigate the interaction and main effects of supplemental Zn and Mn levels on growth, tissue mineral uptake, and immune response in broiler chicken. A basal diet of corn-soybean meal was supplemented with Zn at 40, 80, or 160 ppm and Mn at 60, 120, or 240 ppm in a factorial pattern to constitute nine experimental diets. Each diet was offered to nine replicates of six chicks in stainless steel battery brooders. At 35 days of age, body weight gain, feed conversion efficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…This represents less than 0.001 ppm (w/v) after the final dilution in the drinking water: much less than the 40 ppm necessary to induce some pharmacological immune modulation in broilers, as a trace mineral itself. 39 Thus, the difference of effects between both groups observed herein cannot be attributed to this mild and equal inorganic zinc contamination of samples; instead, the very small amounts of pre-thymulin peptide present in water e if one consider the possibility of molecular non-homeopathic activity e could be linked to the zinc present in diet, at the moment of feeding by the experimental birds. To better define which mechanism is involved in these findings, further experiments using larger number of animals and higher homeopathic pre-thymulin dilutions will be the next step.…”
Section: Discussionmentioning
confidence: 70%
“…This represents less than 0.001 ppm (w/v) after the final dilution in the drinking water: much less than the 40 ppm necessary to induce some pharmacological immune modulation in broilers, as a trace mineral itself. 39 Thus, the difference of effects between both groups observed herein cannot be attributed to this mild and equal inorganic zinc contamination of samples; instead, the very small amounts of pre-thymulin peptide present in water e if one consider the possibility of molecular non-homeopathic activity e could be linked to the zinc present in diet, at the moment of feeding by the experimental birds. To better define which mechanism is involved in these findings, further experiments using larger number of animals and higher homeopathic pre-thymulin dilutions will be the next step.…”
Section: Discussionmentioning
confidence: 70%
“…Similar results were also reported by Gajula et al . () in the liver and Huang et al . () in the pancreas of broilers.…”
Section: Discussionmentioning
confidence: 85%
“…A similar report was also found for Mn accumulation when the Zn inclusion rate was more than 80 mg/kg (Gajula et al . ). Thus, the unaffected Cu and Mn deposition in the measured tissues (blood, liver, tibia, yolk and pancreas), similar to the finding by Bao et al .…”
Section: Discussionmentioning
confidence: 99%
“…The current results of feed consumption agreed with Puchala et al [30] who reported that adding of graded levels of organic Zn (15,30,45 and 60 ppm/ kg diet) to broiler chickens did not significantly affect their feed intake when compared with the inorganic Zn. Control: group supplemented with inorganic zinc oxide; 2 Organic-Zn: group supplemented with Zn methionine; 3 Nano-ZnO: group supplemented with nano Zn-oxide; 4 Zn-mix: group supplemented with both Zn methionine and nano Zn-oxide; 5 TAG: Triglyceride; 6 HDL-C: High-density lipoprotein; 7 VLDL-C: Very low-density lipoprotein; 8 AST: Aspartate amino transferase; 9 ALT: Alanine amino transferase; 10 MDA: Malondialdehyde; 11 CuZn-SOD: Cu/Zn superoxide dismutase. a-b-c Means in a row with different superscripts were significantly different (P<0.05).…”
Section: Performance Parametersmentioning
confidence: 99%
“…In the gastrointestinal tract, the inorganic Zn combined with phytic acid found in most of the broilers grains based diets thus impair zinc and calcium absorption [8], consequently affected the tissue uptake of Zn. Nevertheless, the degree of mineral absorption based on the synergism (Zn and Mn) or antagonism (Zn and Cu) of different minerals [9]. In contrast, organic minerals which combined with aminoacids did not interact with phytic acid as they are lacking the free divalent cations needed for chelation in the intestine [10] and thus, they are metabolized in diverse way to facilitate their absorption [11].…”
Section: Introductionmentioning
confidence: 99%